2019
DOI: 10.1108/tlo-04-2018-0080
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multi-level learning framework

Abstract: This paper examines multiple learning cycles across a UK housebuilder organization following changes made to their Quality Management routine at the organizational level, through to subsequent understanding and enactment at the level of the individuals involved. Design/methodology/approach This study uses a qualitative case study methodology based on an analysis of six-weeks of participant observation, semi-structured ethnographic interviews, and documentation within three of the organization's regional office… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…If personal career planning is consistent with organizational innovation, individuals and organizations will form a more cohesive bond [20]. Once the occupation is positioned as a work goal, technical personnel will be more active in innovative behavior [21]. Career planning ability is beneficial to personal innovative behavior [20].…”
Section: Career Planning's Effect On Individual Continuous Learning Amentioning
confidence: 99%
See 2 more Smart Citations
“…If personal career planning is consistent with organizational innovation, individuals and organizations will form a more cohesive bond [20]. Once the occupation is positioned as a work goal, technical personnel will be more active in innovative behavior [21]. Career planning ability is beneficial to personal innovative behavior [20].…”
Section: Career Planning's Effect On Individual Continuous Learning Amentioning
confidence: 99%
“…We regarded the organizational climate as the subjective norm of innovative behavior, reflecting the possible impact of the environment perceived by engineers on innovative behavior. Morland found that there are four levels of continuous learning: individual, team, region, and organization [21]. Time, communication, and trust within the organization are not only interrelated but also affect the causes of continuous learning and cross-level learning [21].…”
Section: Organizational Climate's Effect On the Mediation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar view, Brix's study of the CBT where communication within the organization is of prominence, Morland et al (2019) in their article "Building better homes: developing a multi-level learning framework for UK housebuilders" point to communication as one of their three inter-related factors that influence learning as information moves across the organizational levels. The authors describe an empirical case study at a large home builder with regions spread across England as they aim to "shed important light on the context surrounding why, when, and how layers of learning synchronize within multi-level organizations" (p. 115).…”
mentioning
confidence: 99%
“…How to make a difference through organizational learning This special issue focuses on exploring the question of how to make a difference through organizational learning [1]. There are several approaches responding to this question, such as building innovation capacity by maintaining ambidexterity in organizational learning using bottom-up approach (Brix, 2019), learning through communication processes (Engström and Käkelä, 2019), enhancing organizational learning with software support systems (Fannoun and Kerins, 2019), creating organizational dynamic capabilities through knowing in practice established through microprocesses (Linden et al, 2019), developing a multi-level learning framework (Morland et al, 2019) and regenerating the learning organization (Pedler and Hsu, 2019).…”
mentioning
confidence: 99%